Homophobic Statements, a Bishop, and the Limits of Freedom of Expression. An In-Depth Commentary on ECtHR 31.08.2023, Amvrosios-Athanasios Lenis v. Greece, no. 47833/20 (Stato, Chiese e pluralismo confessionale, 2024)
Dichiarazioni omofobe, un vescovo e i limiti della libertà di espressione. Un commento approfondito su CEDU 31.08.2023, Amvrosios-Athanasios Lenis v. Greece, no. 47833/20.ABSTRACT: The decision of the ECtHR of 31.08.2023, Amvrosios-Athanasios Lenis v. Greece (no. 47833/20), is a further step toward an increasingly dense jurisprudence on “hate speech” and the limits of freedom of expression. The public proclamation of religious doctrines that are in conflict with the values of the contracting States enshrined in the ECHR is protected to a certain extent by the fundamental right of freedom of religion and belief. However, the qualification of a statement as religious does not justify “hate speech.” The AUTHOR shows the tension between freedom of religion, freedom of expression, and protection against discrimination, and analyzes the decision against the backdrop of Article 17 of the ECHR (prohibition of abuse of rights).SOMMARIO: 1. Preliminary Remarks - 2. The Concept of Hate Speech - 3. The Facts of the Case - 4. The Procedure and Reasoning of the Court - 4.1 The ECtHR’s Preliminary Considerations on Fundamental Rights - 4.2 Legal assessment - 4.3 Some Remarks on (the Non-Invoked) Article 9 of the ECHR - 5. Concluding Remarks.